Comparison of Medical and Surgical Management Options for Incomplete Abortion (Medical Forum Monthly, 2024)
Objective: To compare the maternal outcome in medical versus surgical management of incomplete abortion.Study Design: Comparative cross-sectional studyMaterials and Methods: This study was conducted at the Department of Obstetrics and Gynaecology Unit II Liaquat University Hospital Hyderabad from 1st August 2015 to 31st July 2016.Materials and Methods: Non-probability purposive sampling of 100 patients was done. During the study period, a total 100 cases of incomplete abortion were enrolled in the study with gestational age <12 weeks and vaginal bleeding with ultrasound showing retained products of conception for comparison analysis. Half of them were given Misoprostol 200 µg twice daily for 5 days, and out of rest, 25 underwent manual vacuum aspiration and 25 underwent conventional evacuation under anesthesia. Maternal outcome was noted and compared in both groups using chi square test.Results: The mean age of women in both study groups was 28.09+5.60 years. Majority of women were multiparous with mean parity 2.90+ 2.25. Mostly the women were at gestational age of 10 weeks. Maternal complications were less in medically treated group (22%) as compared to surgically treated group (46%) with P-value 0.011.Patients who underwent Manual vacuum aspiration had lesser infection rates than those who underwent evacuation under anaesthesia (P-value=0.022).Conclusion: Medical treatment is the safest method to offer to a women with retained products of conception with least side effects and no hospital stay. Manual vacuum aspiration is a safe alternate to evacuation under anaesthesia where medical treatment fails or is contraindicated.